Performance evaluation of solar thermal systems as an alternative for human waste treatment. (October 2021) - Delhiraja, Krithika; Sharon, H.; Reddy, K.S.; Philip, Ligy
Graphical abstract: Highlights: Human waste treatment using solar thermal systems was examined. Titled partitioned basin solar distiller showed good recovery of treated water. Stepped solar dryer yielded nutrient rich soil conditioner. Enviro-economic assessment showed proposed system is highly feasible. Abstract: Human waste treatment using renewable energy is one of the emerging interests to minimize adverse environmental impacts. In the present study, the concept of treating urine and faeces separated from blackwater originated from toilets, using indigenously developed solar thermal systems, namely tilted partitioned basin solar distiller (TPBSD) and stepped solar dryer (SSD), respectively were proposed and experimented. The performance of solar thermal units was monitored with respect to temperature, solar radiation, treated water and solids quality, environmental and cost benefits. TPBSD produced a maximum yield of 4.67 ± 0.99 L/m 2 d with a thermal efficiency of 49% during urine distillation. The overall efficiency of solar distiller in terms of recovery varied from 50 to 60%. The condensate quality was found to be good and can be reused for domestic purposes. Similar to the distiller, the SSD performed well for theremoval of moisture content (95.8%) and pathogens (>98.9%). The dried matter was completely free from microbial content and rich in nutrients, which can be used as a natural fertilizer. The kinetics drying was modeled using different thin layer models and among that Page model predicts well with the experimental data. Moreover, the enviro-economic analysis indicated that the TPSBD and SSD could mitigate 23.8 and 6.47 tons of CO2 emissions, respectively, during its 20 years of life span. The energy payback period is 1.97 and 5.19 years, with 300 clear days for TPSBD and SSD, respectively. The obtained results from this research confirm and justify the capability of solar thermal systems as an efficient and viable alternative for human waste treatment.